KALIMAT TANYA DALAM NOVEL THE CONFESSION KARYA JOHN GRISHAM - Wangkai, Debora Selvie (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This research entitled â€œKalimat Tanya dalam Novel The Conffesion Karya Jhon Grishamâ€ is written to fulfill the requirement of finishing S1 degree in Faculty of Letter The aim of the research is to identify, to describe and to analyze interrogative sentence in terms of its types. In analyzing the data, the writer uses descriptive method and by using the concept of Aarts and Aarts about interrogative sentence in terms of its types. The result of this research shows that interrogative sentence has five types which areÂ yes/no questionÂ question tagÂ interrogative sentence formed by question word Wh-word, interrogative sentence in use negative form, and interrogative sentence indefinitely. The type interrogative sentence formed by question word Wh-word is used mostly by the characters. ______________________________________________________________________ Keywords: Interrogative sentence, Novel The Confession, Research